Evaluation of a food safety training intervention in an asylum-seeking population in Rome. (30th September 2020) - Pattavina, F; Barbara, A; Cruciani, I; Calabrese, A C; Mazzetta, E; Sezzatini, R; Tuti, F; Laurenti, P
Abstract: The integration of asylum seekers is a public health issue in various contexts, including food, where they often work. According to European legislation, every food operator is obliged to follow training courses on food safety knowledge in order to prevent food-borne diseases. This study aims to evaluate a food safety training intervention in a population of asylum seekers in Rome through the use of a specific tool validated by the WHO, to introduce them in of catering. The 'Five Key Points for Safer Food' manual was used to deliver the course. An evaluation test for participants to assess the impact of the food safety training is included, divided into 4 categories: General Information, Knowledge (11 items), Attitudes (10) and Behavior (10). The involved food handlers received the same test before and after training. In order to evaluate the effectiveness of the training intervention, the difference in the average of correct pre and post-test answers, overall and by category, was analyzed. Overall, the 69 food handlers comprised 34 (49.3%) females and 35 (50.7%) males, from different continents (36.2% from Africa, 30.5% Central-South America and 33.3% Asia). The 57.3% has previously worked as cook or waiter. The average age was 36.6 (±12.5) with 11.4 (±3.9) years of education. Overall, the average of correct answers increases of 11.6% (from 76.4% to 88.0% correct answers pre and post-test; p < 0.0001). Knowledge pre test was 7.7 (±1.4), while post test was 8.9 (±1.7) (p < 0.0001). Attitude pre test was 8.3 (±2.2), post test was 9.6 (±0.9) (p < 0.0001). Behavior pre test was 7.7 (±2.2), post test 8.8 (±1.9) (p < 0.0001). Despite cultural and linguistic differences, our training intervention has been effective in improving knowledge, attitudes and behaviors on food safety in the target population. The food safety in these contexts cannot be understood only as the fulfilment of a regulatory obligation, but also as an opportunity for aggregation and social integration. Key messages: Food cooking represents a social integration tool: asylum seekers from the most disadvantaged countries could prepare safe multi-ethnic dinners based on the typical courses of their country of origin. WHO training intervention on food safety was effective in improving knowledge, attitudes and behaviors in the target population.